What have we learned about the processes involved in the Iowa Gambling Task from developmental studies? - Cassotti, Mathieu; Aïte, Ania; Osmont, Anaïs; Houdé, Olivier; Borst, Grégoire (Frontiers in Psychology, 2014)
Developmental studies using the Iowa Gambling Task (IGT) or child-friendly adaptations of the IGT converged in showing that children and adolescents exhibit a strong bias in favor of disadvantageous choices whereas adults learn to decide advantageously during the course of the task. In the present article, we reviewed developmental studies that used the IGT or child-friendly adaptations of the IGT to show how these findings provide a better understanding of the processes involved in decision-making under uncertainty. For instance, developmental studies have underlined that until late adolescence, the dominant strategy is to focus only on the frequency of punishment and to choose among options with infrequent losses. Indeed, school-aged children and adolescents’ choices in the IGT seem to be guided by the loss frequency leading them to fail in distinguishing between advantageous and disadvantageous options. In addition, recent developmental studies revealed that adults switch less often after losses than school-aged children and adolescents. These findings suggest that psychological tolerance to loss may facilitate learning the characteristics of each option, which in turn improves the ability to choose advantageously. In conclusion, developmental studies help us refine our understanding of decision-making.